Quantitative Ultrashort Echo Time (UTE) Magnetic Resonance Imaging of Bone: An Update - Ma, Ya-Jun; Jerban, Saeed; Jang, Hyungseok; Chang, Douglas; Chang, Eric Y.; Du, Jiang (Frontiers in Endocrinology, 2020)
Bone possesses a highly complex hierarchical structure comprised of mineral (~45% by volume), organic matrix (~35%) and water (~20%). Water exists in bone in two forms: as bound water (BW), which is bound to bone mineral and organic matrix, or as pore water (PW), which resides in Haversian canals as well as in lacunae and canaliculi. Magnetic resonance (MR) imaging has been increasingly used for assessment of cortical and trabecular bone. However, bone appears as a signal void on conventional MR sequences because of its short T2*. Ultrashort echo time (UTE) sequences with echo times (TEs) 100–1,000 times shorter than those of conventional sequences allow direct imaging of BW and PW in bone. A series of quantitative UTE MRI techniques has been developed for bone evaluation. UTE and adiabatic inversion recovery prepared UTE (IR-UTE) sequences have been developed to quantify BW and PW. UTE magnetization transfer (UTE-MT) sequences have been developed to quantify collagen backbone protons, and UTE quantitative susceptibility mapping (UTE-QSM) sequences have been developed to assess bone mineral.